Exercise of Power and Urban Space. Towards a Theoretical-political Reflection on Architecture and Urban Planning - Valentina Antoniol (University of Bologna, 2021)
In Paris, Capital of the 19th Century, Benjamin states that the goal of Haussmann’s renovation of Paris was to avert civil war. This essay aims to explore this insight and to investigate it also in relation to the transformations of Barcelona by Cerdá. Relying on observations made by Foucault and Schwarte, the article will show that architecture and urban planning can be understood both as political tools that are deployed to manage conflict, and as elements that shape conflict.